Global trends in chronic kidney disease mortality and disability-adjusted life years attributable to low physical activity (1990–2021): a growing public health challenge - ZhenYi Zhao; Jing Mi; HaoDong Jin; ShuaiRan Li; Xia Bai (BMC Nephrology)
Abstract Background Low physical activity (LPA) is a major contributor to the global burden of chronic kidney disease (CKD). Our goal was to assess the spatiotemporal trends in the CKD burden attributable to LPA from 1990 to 2021, with a focus on the globe, China, five SDI regions, and four continents. Methods We analysed CKD-related deaths, DALYs, the ASMR, the ASDR, and the EAPC attributable to low physical activity (LPA). This study focused on trends from 1990 to 2021 across the globe, China, five SDI regions, and four continents. Decomposition analysis, frontier analysis, and forecasting models were employed to explore changes in these indicators and their influencing factors. Results In 2021, CKD attributable to low physical activity (LPA) resulted in 913,070 [95% UI: 348,170–1,619,770] DALYs and 40,920 [95% UI: 16,170–72,560] deaths globally, both of which were higher than those reported in 1990. The AOSD increased from 9.63 (95% UI: 3.73–17.02) to 10.81 (95% UI: 4.14–19.18) per 100,000, with an EAPC of 0.42 (95% CI: 0.35–0.48). The ASMR increased from 0.42 (95% UI: 0.17–0.74) to 0.50 (95% UI: 0.20–0.90) per 100,000, with an EAPC of 0.65 (95% CI: 0.57–0.73). The burden was greater among females, with more rapid increases in the ASDR and ASMR. The Americas and high-SDI regions presented the greatest growth in DALY and mortality rates. Conclusions The burden of CKD attributable to low physical activity (LPA) has increased significantly, particularly in low-SDI regions, women, and elderly individuals. The findings highlight the importance of promoting physical activity and implementing early interventions to inform public health policies. Clinical trial number Not applicable.